Gamification and Technological Resources: Innovative Expe-riences to Motivate and Optimize the Learning Process in University Contexts - Carrión Candel, Elena; de-la-Peña, Cristina; Chaves-Yuste, Beatriz (Digital Education Review, 2026)
The use of gamified technological tools represents an alternative pedagogical practice to enhance the teaching-learning process in higher education. Teachers should employ innovative strategies that foster active, meaningful, and interactive learning in the classroom. This research aims to determine whether the implementation of digital resources based on gamification—Genially, Nearpod, Educaplay, and Quizizz—improves students' evaluation of learning (in terms of knowledge acquisition, teacher training, and motivation) in both face-to-face and online courses across various social science disciplines in higher education. A pre-experimental design was used with pre- and post-intervention measurements conducted over four months (n=345). The results reveal significant improvements in students’ perceptions of teaching style, methodological innovation, content comprehension, problem solving, motivation, participation, and collaborative work. In addition, higher levels of digital competence, self-assessment, and adaptability to new digital resources were observed. Taken together, these findings confirm that gamification supports active, meaningful, and autonomous learning, consolidating its role as an effective strategy in higher education.
Keywords: gamification; higher education; technological tools; digital competence; spiral model of ICT-LKT-EPT competence